2008
DOI: 10.1039/b717307e
|View full text |Cite
|
Sign up to set email alerts
|

Electronic spectroscopy of benzo[g,h,i]perylene and coronene inside helium nanodroplets

Abstract: We have recorded the electronic spectra of benzo[g,h,i]perylene and coronene and their van der Waals complexes with argon and oxygen with a helium-nanodroplet depletion spectrometer. These molecules differ by the addition of one and two fused benzene rings to perylene, which was previously studied in helium. The coronene spectrum is similar to a previously reported jet-cooled laser-induced fluorescence (LIF) spectrum. The van der Waals complexes with argon and oxygen show different complexation sites and maxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 43 publications
1
24
0
Order By: Relevance
“…In their electronic spectroscopy experiment on argoncoronene complexes inside He droplets, Birer et al [31] observed two redshifted peaks in the S 1 ← S 0 spectrum which were assigned to clusters where one Ar atom was localized on the outer rings or over the central hollow, respectively. A third peak appeared with increasing Ar pressure which was subsequentely attributed to the presence of two Ar atoms, although nothing could be stated regarding the precise position on the coronene plane.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In their electronic spectroscopy experiment on argoncoronene complexes inside He droplets, Birer et al [31] observed two redshifted peaks in the S 1 ← S 0 spectrum which were assigned to clusters where one Ar atom was localized on the outer rings or over the central hollow, respectively. A third peak appeared with increasing Ar pressure which was subsequentely attributed to the presence of two Ar atoms, although nothing could be stated regarding the precise position on the coronene plane.…”
Section: Discussionmentioning
confidence: 99%
“…The authors suggested in their analysis a possible competition between helium and argon atoms to occupy favourable docking sites on the molecular substrate. Redshifted peaks in the electronic spectra of argon-coronene clusters inside helium nanodroplets were interpreted in terms of the location of the Ar atoms in the spectroscopic study by Birer et al [31]. A similar investigation was performed recording the laser-induced fluorescence spectra of tetracene complexes in 4 He droplets with increasing pressures of Ne [50].…”
Section: Introductionmentioning
confidence: 88%
“…Experimental data [11,12] and other theoretical [11,13] where available are also included. As these systems attract attention on their own, experimental and theoretical studies on their spectroscopy as well as on substituted forms continue to appear [14]. The present work is focused on the transitions of relevance to the fluorescent sensor systems and the spectroscopy of the fluorophores, in general, is not considered here.…”
Section: Calculations and Resultsmentioning
confidence: 98%
“…For example, studies on benzo[g,h,i]perylene show that in a helium environment the S 2 band origin is significantly broadened. 73 This has been attributed to an enhanced S 2 -S 1 internal conversion in liquid helium. Even more striking are the effects on the photochemistry of 3-hydroxyflavone.…”
Section: Resultsmentioning
confidence: 99%